Voltage Mode Astable Multivibrator Using Single CDBA. (7th April 2013) - Pandey, Rajeshwari; Pandey, Neeta; Paul, Sajal K.; Anand, Kashish; Gautam, Kranti Ghosh
Abstract : This paper aims at presenting three voltage mode square wave generator circuits using single current differencing buffered amplifier (CDBA), a recently proposed mixed mode building block. The first proposed circuit produces a variable frequency output having fixed duty cycle, whereas the rest of the circuits have variable duty cycle. One of the circuits uses passive element adjustment to control the duty cycle, whereas electronic control is used in the other circuit. The workability of the proposed circuits is confirmed through SPICE simulations and experimental work.